Sustainable cassava commodity agribusiness system in East Lampung Regency - Zulkarnain; Isnaini, Soni; Maryati (Fakultas Pertanian Universitas Yudharta Pasuruan, 2024)
Introduction: The agribusiness system is a series of sustainable business management from upstream to downstream. Cassava farming is one of the strategic food crops that supports the national economy. Increasing cassava commodities cannot be separated from implementing an effective and efficient agribusiness system. The research aims to examine the sustainable cassava commodity agribusiness system in East Lampung Regency. Methods: The total population of cassava farmers in East Lampung Regency is 478 farmers. The sampling technique refers to the Sugiarto formula so 48 cassava farmers were obtained using a simple random sampling technique. Data analysis is 1) procurement of production facilities using a Likert scale, 2) farming using income analysis, 3) processing using added value, 4) marketing using marketing channels, marketing margins, and Farmer Share, and 5) Supporting institutional services. Results: Research results 1) Procurement of production facilities are in the category of being used. 2) cassava farming is profitable 3) processing cassava into tiwul products provides added value. 4) marketing of fresh and processed cassava is included in efficient marketing, and 5) supporting institutions have not contributed to cassava commodities. Conclusion: The cassava commodity agribusiness system has been established but the supporting services are not yet running well, so it is necessary to develop integrated agribusiness institutions.